Comparative safety and short-term outcomes of intraoperative radiotherapy versus neoadjuvant chemoradiotherapy in locally advanced rectal cancer: a retrospective study - Gong, Zhijie; Li, Yingze; Zhou, Jun; Deng, Yanjie; He, Yinghao; Wang, WeiWei; Yang, Qiangbang; Pan, Jian; Ma, Minghui (Frontiers in Surgery, 2026)
PurposeNeoadjuvant chemoradiotherapy (nCRT) constitutes an integral component of the standard therapeutic strategy for locally advanced rectal cancer (LARC) but carries cumulative toxicity, cost, and occasional non-response. Intraoperative radiotherapy (IORT) delivers a single high dosage directly to the tumor bed and may overcome these limitations. We compared short-term efficacy and safety of low-kilovoltage(kV) x-ray IORT with long-course nCRT.MethodsLARC patients treated at Maoming People's Hospital (2022–2024) were retrospectively reviewed. The nCRT cohort received 45–50 Gy radiotherapy plus capecitabine before surgery; the IORT cohort underwent INTRABEAM low-kV x-ray IORT (12.5–20 Gy) during surgery. Disease-free survival (DFS), overall survival (OS), postoperative complications, and recurrence were analyzed. Survival was estimated by Kaplan–Meier curves.ResultsA total of 67 patients were included (46 in nCRT, 21 in IORT). Kaplan–Meier analysis showed no significant difference in DFS or OS between the IORT and nCRT groups (DFS P = 0.669; OS P = 0.864). 3-year DFS (53.7% vs. 52.8%, P = 0.669) and OS (89.0% vs. 78.4%, P = 0.864) did not differ between IORT and nCRT. Early postoperative bowel obstruction and urinary retention were more frequent after IORT, although neither difference was significant; long-term complications and recurrence patterns remained comparable between the groups.ConclusionSingle-fraction low-kV IORT provides short-term survival equivalent to standard nCRT with acceptable perioperative safety. It is a viable option for LARC patients unable or unwilling to undergo prolonged nCRT, although vigilance for early gastrointestinal and urinary complications is warranted.